Air-Sea Latent Heat Flux Anomalies Induced by Oceanic Submesoscale Processes: An Observational Case Study - Song, Xiangzhou; Xie, Xuehan; Qiu, Bo; Cao, Haijin; Xie, Shang-Ping; Chen, Zhiqiang; Yu, Weidong (Frontiers in Marine Science, 2022)
The classical theory predicts that a geostrophically balanced mesoscale eddy can cause a sea surface temperature (SST) anomaly related to Ekman pumping. Previous studies show that an eddy-induced SST anomaly can result in a sea surface latent heat flux (LH) anomaly at a maximum magnitude of O(10) Wm^-2, decaying radially outward from the center to the margin. In this study, we investigate the LH anomalies associated with submesoscale processes within a cyclonic eddy for the first time using recent satellite-ship-coordinated air-sea observations in the South China Sea. Unbalanced submesoscale features can be identified as submesoscale SST fronts. Along the ship track, the SST strikingly decreases by 0.5 °C within a horizontal distance of 1.5 km and increases quickly by 0.9 °C with a spatial interval of 3.6 km. The along-track SST is decomposed into three parts: large-scale south-north fronts and anomalies induced by mesoscale and submesoscale motions. Our analysis shows that the amplitude of the LH anomaly induced by the mesoscale SST anomaly is 12.3 Wm^-2, while it is 14.3 Wm^-2 by unbalanced submesoscale motions. The mean (maximum) spatial gradient of the submesoscale LH anomalies is 1.7 (75.7) Wm^-2km^-1, which is approximately 1.5 times those (1.2 Wm^-2km^-1 and 59.9 Wm^-2km^-1) in association with mesoscale eddies. The spectra of LH and SST anomalies show similar peaks at 15 km before sloping down with a power law between k^-2 and k^-3, indicating the underlying relationship between the LH variance and submesoscale processes.